Molecular mechanisms underlying the models of neurodevelopmental disorders in maternal immune activation relevant to the placenta. (17th January 2019) - Tsukada, Tsuyoshi; Shimada, Hiroki; Sakata‐Haga, Hiromi; Iizuka, Hideaki; Hatta, Toshihisa
Abstract : The rapid rise in the prevalence of autism spectrum disorders (ASD) and other psychiatric disorders displaying similar traits has increased the need to elucidate their molecular mechanisms. Epidemiological studies have shown that maternal infection during mid‐pregnancy is associated with increased risk of neurodevelopmental disorders such as ASD in offspring. Using maternal infection models, researchers have gathered evidence relevant to such disorders. A comprehensive summary of the changes in the brain structure, function, and behavior in offspring induced by maternal immune activation (MIA) has been reported. However, the molecular mechanisms underlying the association between MIA and improper brain development, which ultimately lead to neurodevelopmental disorders, have not been fully reviewed. This paper summarizes the currently known molecular mechanisms associated with the MIA model, with a special focus on the role of the placenta in fetal brain development.